The Role of Islamic Work Motivation and Islamic Work Culture on Work Productivity of Employee: Survey in House of Finance and Fiance (Baitul Mal Wat Tamwil (BMT) in Pontianak City - Syaifullah, Muhammad; Shohibah, Anis (Khatulistiwa, 2019)
This research examines the Role of Islamic Work Motivation and Islamic Work Culture on BMT Employee Productivity in Pontianak City. The renewal of this research compared to previous research is the development of theories from previous studies; Research Period; The phenomenon of expert statements and with reference sources from different bona fide media; References to variable theories and dimensions and indicators used differ. This study uses primary and secondary data sources. Data collection tools using questionnaires (questionnaires), measuring instruments using validity and reliability tests to see the validity of the results of research and reliability testing with alpha Croanbach, then analyze the data using the method of multiple regression analysis. The results of this study prove that simultaneously Islamic Work Motivation variables and Islamic Work Culture play a positive role in BMT Employee Productivity in Pontianak City, which is equal to 77.001. The partial effect of the results of the T test shows that the value of Islamic Work Motivation (X1) is 0,013 and the Work Value of Islamic Culture (X2) is 0,432. The independent variable (Motivation of Islamic Work and Islamic Culture) is only able to explain the independent variable 78,6%, while the remaining 21,4% is explained by other variables not examined in this study.